A Case of Persistent Bacillus cereus Bacteremia Responding to a Combination of Vancomycin and Gentamicin - Hiroshi Sasano; Toshihiro Yoshizawa; Mai Suzuki; Yukiko Fukui; Ryutarou Arakawa; Naoto Tamura; Toshio Naito (Case Reports in Infectious Diseases)
A 56-year-old woman with a history of connective tissue disease developed fever, and Bacillus cereus (B. cereus) was detected in blood cultures. Therefore, treatment with vancomycin (VCM) was initiated. Since her blood cultures persistently detected B. cereus despite peripheral intravenous catheter replacement and VCM treatment, concomitant treatment with gentamicin (GM) was started. Blood cultures then became negative. Persistent B. cereus bacteremia responded to combination therapy with VCM and GM. This combination therapy may increase the risk of developing renal dysfunction, but the risk can be mitigated by appropriate therapeutic drug monitoring (TDM) and dose adjustments to achieve successful treatment.